Agua de servicio público y su incidencia en la salud de los habitantes de La Parroquia Clemente Baquerizo del cantón Babahoyo - Murillo Santillan, Wilmer Alexis (2021)
This investigation was carried out in the Clemente Baquerizo parish sector of the Babahoyo Canton, in this investigation we want to determine the quality of the public service water generated by the drinking water treatment plants of the Babahoyo Canton to determine its level of purification that it contains and If it is an act for consumption directly by the inhabitants of the Clemente Baquerizo parish, either for domestic use or for the preparation of food or food, and to know what serious its impact on the health of the inhabitants of the Clemente parish Baquerizo. In this way, it will be possible to evaluate what would be the impact on the health of the inhabitants of said parish and thus strengthen the knowledge about the correct purification of public service water and what methods should be used to guarantee a correct purification and purification of the water, to seek an excellent quality of drinking water for the health of the inhabitants of the Clemente Baquerizo parish by making known what the Biological risks would be when ingesting public service water directly. Through this content to be able to make known which would be the most optimal levels in terms of water quality and contribute to the improvement and its good use in a domestic way, guaranteeing the physical and mental health of young people, having more knowledge of the different types of implement water purification in homes.